Longitudinal regret after treatment for low‐ and intermediate‐risk prostate cancer. Issue 21 (5th July 2017) - Hurwitz, Lauren M.; Cullen, Jennifer; Kim, Daniel J.; Elsamanoudi, Sally; Hudak, Jane; Colston, Maryellen; Travis, Judith; Kuo, Huai‐Ching; Rice, Kevin R.; Porter, Christopher R.; Rosner, Inger L.
Abstract : BACKGROUND: Prostate cancer patients diagnosed with low‐ and intermediate‐risk disease have several treatment options. Decisional regret after treatment is a concern, especially when poor oncologic outcomes or declines in health‐related quality of life (HRQoL) occur. This study assessed determinants of longitudinal decisional regret in prostate cancer patients attending a multidisciplinary clinic and treated with radical prostatectomy (RP), external beam radiation therapy (EBRT), brachytherapy (BT), or active surveillance (AS). METHODS: Patients newly diagnosed with prostate cancer at the Walter Reed National Military Medical Center who attended a multidisciplinary clinic were enrolled into a prospective study from 2006 to 2014. The Decision Regret Scale was administered at 6, 12, 24, and 36 months posttreatment. HRQoL was also assessed at regular intervals using the Expanded Prostate Cancer Index Composite and 36‐item RAND Medical Outcomes Study Short Form questionnaires. Adjusted probabilities of reporting regret were estimated via multivariable logistic regression fitted with generalized estimating equations. RESULTS: A total of 652 patients met the inclusion criteria (395 RP, 141 EBRT, 41 BT, 75 AS). Decisional regret was consistently low after all of these treatments. In multivariable models, only African American race (odds ratio, 1.67; 95% confidence interval, 1.12‐2.47) was associated with greater regret across time. Age and control preference were marginally associated with regret. Regret scores were similar between RP patients who did and did not experience biochemical recurrence. Declines in HRQoL were weakly correlated with greater decisional regret. CONCLUSION: In the context of a multidisciplinary clinic, decisional regret did not differ significantly between treatment groups but was greater in African Americans and those reporting poorer HRQoL. Cancer 2017;123:4252–4258. © 2017 American Cancer Society . Abstract : Among low‐ and intermediate‐risk prostate cancer patients receiving care at a multidisciplinary clinic, decisional regret is low 3 years after treatment. Decisional regret does not differ significantly between treatment groups but is greater in African American patients and in patients reporting poorer HRQoL.